Steganographic Secure Data Communication – A Hardware Approach - Naik, A. N.; Patil, R.T.; Naik, N.B. (Asian Journal of Electrical Sciences, 2013)
Steganography is a science dealing with writing hidden messages in a particular way that only the sender & the intended recipient are able to decipher so as to provide security in open environment like internet. Steganography attempts to hide the very existence of the message and make communication undetectable. Important domains, besides classic computing, where steganography can be applied are domains using mobile and embedded devices. This paper focuses on the implementation of a steganographic algorithm on embedded devices – microcontrollers. Furthermore, this article presents experimental results obtained from testing a steganographic algorithm on embedded devices. The main purpose of implementing such an algorithm on a microcontroller is to provide security on low and medium cost mobile and other dedicated devices [1].